Long‐term administration of alpha‐1 blocker can reverse the micturition pattern in a bladder outlet obstruction murine model. (27th September 2020) - Kitta, Takeya; Chiba, Hiroki; Kanno‐Kakibuchi, Yukiko; Hattori, Tsuyoshi; Higuchi, Madoka; Ouchi, Mifuka; Togo, Mio; Abe‐Takahashi, Yui; Michishita, Mai; Kitano, Tatsuya; Shinohara, Nobuo
Abstract : Objective: To investigate the effect of chronic administration of an alpha‐1 blocker on micturition patterns in long‐term partial bladder outlet obstruction. Methods: Mice were divided into three groups: a normal group, in which animals were fed a standard diet; a partial bladder outlet obstruction group, in which the proximal urethra was tied and animals were fed a standard diet; and a partial bladder outlet obstruction + naftopidil group, in which the proximal urethra was tied and animals were fed a standard diet containing naftopidil. Micturition behavior was evaluated in all groups for 6 months after partial bladder outlet obstruction surgery. The parameters evaluated included voided volume, time per void, urination frequency and total urine volume. Quantitative assessment of gene expression was also carried out. Results: Total urine volume, as well as total and average voided volume during night, was significantly decreased in partial bladder outlet obstruction + naftopidil mice compared with partial bladder outlet obstruction animals. The levels of transcripts encoding 5‐hydroxytryptamine 2A and tissue inhibitor of metalloproteinase 2 were significantly decreased in the partial bladder outlet obstruction + naftopidil group compared with the partial bladder outlet obstruction group. Conclusions: Long‐term administration of an alpha‐1 blocker seems to reverse the disturbance of the micturition pattern caused by partial bladder outlet obstruction. Mechanistically, this effect might be mediated by changes in the expression of a serotonin receptor and/or in the activity of the fibrogenesis pathway.